Sodobna zgodovina v osnovnih in srednjih šolah v socialistični Sloveniji, 1945-1990 - Režek, Mateja (Prispevki za novejšo zgodovino, 2020)
The article discusses the teaching of contemporary history in primary and secondary schools in the socialist Slovenia/Yugoslavia based on the systematic overview and analysis of school curricula and history textbooks between 1945 and 1990. The research focuses on the political use of history as one of the key instruments of legitimising the communist rule. Its main legitimation points were the National Liberation Struggle during World War II, anti-fascism, and the social revolution. Another important legitimising tenet was the concept of resolving the national question; i.e. the principle of brotherhood and unity. After the split between the Soviet Union and Yugoslavia in 1948, Tito%s resistance to Stalin, self-management, and non-alignment also entered the historical canon as the specific qualities of the Yugoslav socialism.
Keywords: collective memory; curricula; history; history teaching; history textbooks; ideologisation; ideologizacija; kolektivni spomin; pouk zgodovine; Slovenia; Slovenija; socialism; socializem; učni načrti; zgodovina; zgodovinski učbeniki